PENGARUH TEMPERATUR UAP AIR NIRA AREN TERHADAP PRODUKSI ALKOHOL SEBAGAI BAHAN BAKAR ALTERNATIF - Paul M. Rumagit; Fransiscus J. Tulung (ROTOR, 2017)
Destilationi Process for making of alcohol by fraksination vapour, can yield rate of high alcohol, with palm water newly tapped as a media. Equipment of Destilation designedly and also constructed from metal substance / stainles steel is a means of the examination, where component of equipments ; basin boiled of water , basin of palm water, channel of fracsination, alcohol arrester, cooler, and the hose of alcohol recervoir. The Examination of method is execute variation of change of temperature vapour palm water in boiled tube. For the vapour temperature 81 0C make the rate of alcohol 95%, vapour temperature 85 0C make the rate of alcohol 90% and the vapour temperature 90 0C yielding rate of alcohol 87%. Alcohol of rate is excelsior at temperature of palm water vapour which lower and also volume result of catching less be accompanied with duration of combustion time. Keyword : Equipment of Destilation, fraksination, alcohol, bio-fuel, palm of water